Simbol Budaya Populer, Lambang Negara dan Kebebasan Berekspresi dalam Perspektif Hukum Pidana Indonesia - Ayu Intan Mutmainah; Asmanul Husna (Universitas Cokroaminoto Yogyakarta, 2026)
The phenomenon of hoisting the fictional One Piece flag (Jolly Roger) during Indonesia’s Independence Day sparked debates on freedom of expression and the protection of state symbols. This study examines the legal boundaries of expression within Indonesian criminal law regarding popular culture symbols. Using a normative legal method and statutory approach, the analysis refers to the 1945 Constitution, Penal Code, and Law No. 24 of 2009. Findings show that hoisting the Jolly Roger is not explicitly prohibited, unless it fulfills criminal elements such as insult or incitement. Such symbols are better viewed as peaceful social critique. The state should prioritize education and dialogue.